Doctors’ performance when using Hospital Information System (HIS) in analysing determinants of mental health - Kartika Sari, Desi; Kiswanto, Kiswanto; Muhardi, Muhardi; Hartono, Budi; Efendi, Ahmad Satria (JOURNAL OF Mental Health Concerns, 2025)
Background: The implementation of hospital information systems is expected to improve employee performance, particularly among doctors as key users. Previous studies have shown that the effectiveness of such systems can positively influence individual performance. Purpose: To analyze of Mental Health and Performance of Doctors Using the Hospital Information System (HIS). Method: This quantitative study used a total sampling technique involving 41 doctors at PRIMA Hospital Pekanbaru. Data were analyzed using multiple linear regression to assess the influence of various factors on doctors’ performance in using HMIS. The independent variables included knowledge, attitude, experience, doctors’ perception, ease of use, system security and reliability, feature–need suitability, data quality and accessibility, hospital policy, training and supervision support, as well as incentives and performance evaluation. Results: The analysis revealed that only the doctors’ perception variable had a statistically significant effect on doctors' performance (p = 0.010 < 0.05). Other variables including knowledge, attitude, experience, ease of use, system security, hospital policies, training, and incentives showed no significant influence (p > 0.05). Conclusion: Doctors’ perception of HMIS is a key factor in enhancing their performance in using the system. To optimize HMIS implementation, hospitals should focus on improving doctors’ understanding and acceptance through strategies such as targeted education and socialization, simplifying and customizing system features, enhancing system speed and interface, and offering performance-based incentives for HMIS utilization. Keywords: Determinants; Doctors’ Performance; Hospital Management Information System; Multiple Linear Regression; Perception.